Research title: (Dramatic structure in writing the cartoon series script): Cartoon series scenario - طاهر حسن, امال (Basrah Arts Journal, 2025)
Introduction: Drama in general, and drama directed at children in particular, remains, to this day, the most expressive and influential human creative activity on individual behavior. Children are the fundamental group in society and its formation. Therefore, drama directed at children is the most expressive and influential human creative activity on individual behavior, contributing to helping them acquire many advantages. Its content includes positive social values ​​that help children distinguish between right and wrong and develop a sense of responsibility. These values ​​are formulated in an entertaining and enjoyable way, indirectly. Therefore, we see animated films being used dramatically to craft stories in a creative way. Here, it is necessary to prepare a text that is appropriate for the story and its events, on the one hand, and the child's perception and comprehension, on the other hand, and to embody it using animated films. Chapter One: The methodological framework, which addresses the research methodology, including the research problem, its objective, and its importance. It also defines the most important terms used in the research title, as well as the research samples and previous studies on the subject. Second: The theoretical framework, which consists of the following sections: Section One: Section One - The Origins of Animation Section Two: Dramatic Structure in Cartoon Series Section Three: Narrative Narrative Patterns in the Series Chapter Three: This section covers the research procedures and the analysis of the selected samples. This section presents the results and conclusions, and also includes a list of footnotes and sources included in the research.